Hydrostatic pressure promotes chondrogenic differentiation and microvesicle release from human embryonic and bone marrow stem cells. Issue 4 (17th January 2022) - Luo, Lu; Foster, Nicola C.; Man, Kenny L.; Brunet, Mathieu; Hoey, David A.; Cox, Sophie C.; Kimber, Susan J.; El Haj, Alicia J.
Abstract: Mechanical stimulation plays in an important role in regulating stem cell differentiation and their release of extracellular vesicles (EVs). In this study, effects of low magnitude hydrostatic pressure (HP) on the chondrogenic differentiation and microvesicle release from human embryonic stem cells (hESCs) and human bone marrow stem cells (hBMSCs) are examined. hESCs were differentiated into chondroprogenitors and then embedded in fibrin gels and subjected to HP (270 kPa, 1 Hz, 5 days per week). hBMSC pellets were differentiated in chondrogenic media and subjected to the same regime. HP significantly enhanced ACAN expression in hESCs. It also led to a significant increase in DNA content, sGAG content and total sGAG/DNA level in hBMSCs. Furthermore, HP significantly increased microvesicle protein content released from both cell types. These results highlight the benefit of HP bioreactor in promoting chondrogenesis and EV production for cartilage tissue engineering. Graphical Abstract and Lay Summary: Mechanical stimulation plays in an important role in regulating stem cell differentiation and their release of extracellular vesicles (EVs). In this study, it is shown that low magnitute hydrostatic pressure (HP) can promote chondrogenic differentiation and microvesicle release from human embryonic stem cells (hESCs) and human bone marrow stem cells (hBMSCs) . Our study highlights the benefit of mechanical stimulation in promoting chondrogenesis and EV production for cartilage tissue engineering.